Microstructure and thermoelectric properties of p-type bismuth antimony telluride nanowires synthetized by template electrodeposition in polycarbonate membranes. (20th July 2018) - Danine, Abdelaadim; Schoenleber, Jonathan; Ghanbaja, Jaafar; Montaigne, François; Boulanger, Clotilde; Stein, Nicolas
Abstract: In this study we report the microstructure and the thermoelectric properties of p-type Bi-Sb-Te 60 nm nanowires using ion track-etched polycarbonate templates for fixed applied potentials. A mixture of Bi +III, Sb +III and Te +IV in specific tartaric-nitric acid electrolyte was prepared in order to obtain the Bi0.5 Sb1.5 Te3 compound. Cathodic linear sweep voltammograms revealed the Te deposition followed by the deposition of Bi-Sb-Te compounds at more negative potentials with defined compositions. X-ray diffraction (XRD) analysis and transmission electron microscopy (TEM) characterizations show polycrystalline and smooth nanowires of 60 nm diameter regardless of the deposition potential. At −0.1 V potential, the nanowires exhibit a chemical content i.e. Bi0.4 Sb1.3 Te3.3 close to the targeted composition. According to HR-TEM analysis, large grains with preferential orientation in [015]* containing twin boundaries were observed. The Te excess can be explained by the presence of over inserted Te atoms into the quintuplet interstices. The nanostructures exhibit semiconducting behavior with positive Seebeck coefficient (+138 μV/K) associated with electrical resistivity (128 μΩ m). Comparative electrical measurements between individual nanowires and bundle of nanowires show that the overall electrical resistance of the membrane/nanowires composite is governed by internal resistance rather than material one. Graphical abstract: Image 1